Pemetaan Komik Indonesia Periode Tahun 1995-2008 - Irawati Tirtaatmadja; Nina Nurviana; Alvanov Zpalanzani Mansoor (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2012)
Indonesia's comics in 1995-2008 are rich in visual and story exploration. It is unfortunate that there are no efforts to do the charting for this creative industry. This research focus is documenting the 1995-2008 Indonesia's comics through systematical and descriptive statistic review. It is an empirical study in order to set the footing for further research on Indonesia's comics especially on 1995-2008 time periods. It is the starting point of the new and rich yet debatable for its origin and identity of Indonesia's comic development. Based on research findings, there are three aspects that generate new Indonesia's comics. They are the competitive spirit that ignites the Indonesia's comic artists to strive in making comics, abundance of visual and sequential reference in elaborating slice of life and enhancing story in comics from translated manga, and lots of comic events held to make the comic artists busy producing comics and promoting towards new and eager to explore the new taste of Indonesia's comics.